A comprehensive study on the production and photocatalytic activity of copper ferrite nanoparticles synthesized by microwave-assisted combustion method as an effective photocatalyst. (November 2022) - Karcıoğlu Karakaş, Zeynep
Abstract: This study was planned in two stages. In the first stage, copper ferrite nanoparticles were synthesized by microwave-assisted combustion method, and the effects of synthesis conditions on structural, magnetic, and morphological properties were investigated. The structural, morphological, and magnetic properties of the samples produced at each stage have been comprehensively characterized. The results obtained indicate that microwave irradiation alone is not sufficient to convert to copper ferrite by microwave-assisted combustion method; for this reason, the precursor sample produced by the microwave effect was subjected to heat treatment at temperatures ranging from 300 °C to 1000 °C, and the effects of the applied heat treatment temperature on the structural morphological and magnetic properties of the produced products were investigated. Accordingly, the optimum value of the heat treatment temperature was determined as 700 °C. In the second part of this study, copper ferrite nanoparticles produced under optimum conditions were used as photocatalysts for dye removal from wastewater by photocatalytic oxidation. In these experiments, the effects of parameters such as initial pollutant concentration, catalyst dosage, initial pH value, temperature, and light intensity on the removal efficiency were investigated. In these experiments, optimum operating conditions were determined as 10 mg/L for initial pollutant concentration, 8 for initial pH value, 0.10 g/L for catalyst dosage, 60 °C for temperature, and 8800 μW/cm 2 for light intensity. The obtained results show that copper ferrite nanoparticles exhibit an excellent photocatalytic activity. Accordingly, it was determined that the most influential parameter for the removal efficiency in this process was the temperature. The effect of the initial pH value was minimal. In addition, it was determined that the temperature significantly increased the reaction rate. Kinetic studies on experimental data obtained from experiments performed with various parameters showed that the process is fully compatible with the pseudo-first-order kinetic model. Highlights: Copper ferrite nanoparticles were successfully synthesized by microwave assisted combustion method. The synthesized particles were used as a photocatalyst for dye removal from synthetically prepared wastewater. In photocatalysis studies, the effects of parameters such as initial pollutant concentration, catalyst dosage, initial pH value, temperature and light intensity on the removal efficiency were investigated. It was determined that the photocatalysis process was fully compatible with the pseudo-first order kinetic model.